Necessary optimality conditions for minimax optimal control problems with mixed constraints - Patzi Aquino, Paola Geovanna; De Pinho, M.D.R.; Silva, Geraldo Nunes [UNESP] (EDP Sciences, 2021)
A weak maximal principle for minimax optimal control problems with mixed state-control equality and inequality constraints is provided. In the formulation of the minimax control problem we allow for parameter uncertainties in all functions involved: in the cost function, in the dynamical control system and in the equality and inequality constraints. Then a new constraint qualification of Mangassarian-Fromovitz type is introduced which allowed us to prove the necessary conditions of optimality. We also derived the optimality conditions under a full rank conditions type and showed that it is, as usual, a particular case of the Mangassarian-Fromovitz type condition case. Illustrative examples are presented.
Keywords: Maximum principle; Minimax optimal control problems; Mixed constrained; Nonsmooth analysis